Flame-retardant, heat-insulating and sound-absorbing composite material and preparation method thereof
By adding zirconium oxychloride, gadolinium nitrate and other materials to the glass fiber composite material, and introducing phase change materials and modified glass fiber, the problems of high thermal conductivity, low flame retardant performance and insufficient sound absorption effect of the composite material are solved, and the Better heat insulation, flame retardant and sound absorption performance.
Patent Information
- Application Number
- CN202411740686.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing glass fiber composite materials have a large thermal conductivity, resulting in poor thermal insulation effect, low flame retardant performance, and insufficient sound absorption effect, which affects its practical application.
By adding materials such as zirconium oxychloride and gadolinium nitrate to the composite material to enhance flame retardant performance, and introducing phase change materials and modified glass fibers to reduce thermal conductivity and improve sound absorption effect.
It effectively reduces the thermal conductivity of the composite material, improves the flame retardant performance and sound absorption effect, enhances the mechanical properties and durability of the material, and ensures its long-term reliability.
Smart Images

Figure BDA0005162548000000151 
Figure BDA0005162548000000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass fiber composite materials, and particularly relates to a flame retardant, heat insulating and sound absorbing composite material and a preparation method thereof. Background Art
[0002] The phenomenon that energy is absorbed by an object during the propagation of sound waves is called sound absorption; any material can absorb sound waves, but the degree of absorption is different. Materials with a certain absorption efficiency are called sound-absorbing materials. Glass fiber is an inorganic non-metallic fiber material made by a series of processes such as high-temperature melting and wire drawing of inorganic non-metallic mineral materials such as limestone, quartz sand, dolomite and leaf wax in a certain proportion. Glass fiber has low thermal conductivity, and the layered structure of glass fiber felt limits the flow and diffusion of air, making glass fiber felt have good sound absorption and heat insulation effects. It can be widely used in architectural acoustics, transportation, aerospace and other fields.
[0003] A Chinese patent (publication number CN111517748A) discloses a high-strength glass fiber composite material and its preparation method, which uses silicon dioxide, graphene oxide and other components to prepare a glass fiber composite material with excellent thermal insulation performance. The composite material has excellent mechanical properties and contains spinning fibers, additives and other components. It can store heat and adjust the temperature of the composite material under high temperature conditions, greatly improving the thermal stability of the composite material. However, the patented technology does not solve the problems of the glass fiber composite material in the prior art, such as the large thermal conductivity, poor thermal insulation effect, low flame retardant performance, and insufficient sound absorption effect, which seriously affects the practical application of the glass fiber composite material.
[0004] Therefore, how to modify the glass fiber in the composite material, add phase change materials, and introduce other modified components to reduce the thermal conductivity of the composite material and improve the flame retardant properties and sound absorption effects has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a flame retardant, heat insulating and sound absorbing composite material and a preparation method thereof, aiming to solve the problems in the prior art that the glass fiber composite material has a large thermal conductivity, resulting in poor thermal insulation effect, low flame retardant performance, and insufficient sound absorption effect.
[0006] The present invention enhances the flame retardant properties of the composite material by adding materials such as zirconium oxychloride and gadolinium nitrate, effectively reduces the flammability of the composite material under high temperature conditions, and improves the safety of the material under extreme conditions; the introduction of phase change materials helps the thermal management of the material, and can absorb and store heat under high temperature environments, thereby providing a good thermal insulation effect; modified glass fibers, basalt fibers and other materials are added, and these fibers have good acoustic properties, which can effectively reduce noise transmission, thereby improving the sound absorption effect; therefore, the present invention not only improves the mechanical properties of the material, but also ensures its good durability and stability, ensuring the long-term reliability of the material
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] A first aspect of the present invention provides a method for preparing a flame retardant, heat insulating and sound absorbing composite material, comprising the following steps:
[0009] Step S1: by weight, 10 to 12 parts of zirconium oxychloride, 6 to 8 parts of gadolinium nitrate, and 3 to 5 parts of polyethylene glycol are added to 80 to 100 parts of deionized water and mixed evenly, 20 to 25 parts of a 2 mol / L sulfuric acid solution are added at 80 to 85° C., and then the temperature is raised to 145 to 150° C. for hydrothermal reaction for 6 to 8 hours. After the reaction is completed, the mixture is cooled to room temperature, ammonia water is added to adjust the pH to 7.5 to 7.8, centrifuged, washed, and dried to obtain a phase change material;
[0010] Step S2: In parts by weight, 20 to 25 parts of glass fiber and 10 to 15 parts of basalt fiber are added to 15 to 20 parts of silica sol and stirred for 20 to 30 minutes, then 4 to 6 parts of the phase change material and 1 to 3 parts of graphene oxide are added and stirred for 30 to 40 minutes, a first aging treatment is performed for 20 to 24 hours, and then 20 to 30 parts of anhydrous ethanol are added for a second aging treatment for 26 to 30 hours, and dried at 80 to 90° C. for 6 to 8 hours to obtain a flame retardant, heat insulating and sound absorbing composite material.
[0011] The phase change material of the present invention is prepared by adding ammonia water and acid solution to a zirconium oxychloride aqueous solution so that part of the Zr 4+ Hydrolysis obtains crystal nuclei, which can then form nano zirconium oxide. At the same time, rare earth elements are introduced. The doping of rare earth elements will introduce impurity atoms into the zirconium oxide lattice, causing lattice distortion. These distortions will scatter phonons (carriers of thermal energy), increase the resistance to heat conduction, and thus reduce the thermal conductivity of the composite material.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the glass fiber is a modified glass fiber; the preparation method of the modified glass fiber comprises: adding 4 to 6 parts of tetrabutyl titanate to 20 to 25 parts of anhydrous ethanol by weight to fully dissolve, then adding 1 to 3 parts of acetylacetone and 10 to 15 parts of deionized water and stirring for 20 to 30 minutes, then adding 6 to 8 parts of nitric acid solution with a molar concentration of 1 mol / L, stirring for 1 to 2 hours to obtain a sol solution; adding 10 to 15 parts of acidified glass fiber and 15 to 20 parts of anhydrous ethanol to 30 to 50 parts of the sol solution, stirring for 50 to 60 minutes, standing for 2 to 4 hours, removing the upper liquid to obtain a precipitate, washing the precipitate with anhydrous ethanol and deionized water in turn, and drying at 70 to 75° C. for 40 to 60 minutes to obtain the modified glass fiber.
[0014] As a preferred technical solution of the present invention, the acidified glass fiber includes acidifying the glass fiber, wherein the acidifying treatment includes: adding 5 to 8 parts of phytic acid to 90 to 100 parts of deionized water to fully dissolve, then adding 10 to 15 parts of glass fiber to soak for 10 to 15 minutes, washing with deionized water after soaking, and drying to obtain the acidified glass fiber.
[0015] As a preferred technical solution of the present invention, the length of the glass fiber is 50 to 300 μm and the diameter is 4 to 6 μm.
[0016] Modified glass fiber contains titanium dioxide, which can absorb heat at high temperatures, reduce the temperature of the material, and slow down the combustion rate. At the same time, titanium has a certain catalytic activity, which can catalyze the generation of non-combustible gas, dilute the concentration of combustible gas, inhibit combustion, and increase the oxygen index of the material. In addition, titanium dioxide particles can form tiny pores in the material. These pores are filled with air, which can increase the loss of sound waves inside the material, thereby improving the sound absorption coefficient.
[0017] As a preferred technical solution of the present invention, the basalt fiber is a boron quantum dot modified basalt fiber; the preparation method of the boron quantum dot modified basalt fiber comprises: adding 10 to 15 parts of basalt fiber to 80 to 100 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L by weight, soaking for 2 to 4 hours at 40 to 50° C., washing with deionized water for 3 times after soaking to obtain a roughened basalt fiber; adding 10 to 15 parts of the roughened basalt fiber to 20 to 25 parts of a boron quantum dot solution, stirring for 40 to 60 minutes, and freeze-drying to obtain a boron quantum dot modified basalt fiber.
[0018] As a preferred technical solution of the present invention, the preparation method of the boron quantum dot solution includes: adding 2 to 4 parts of ammonium pentaborate and 1 to 2 parts of boric acid to 20 to 25 parts of deionized water by weight, stirring for 1 to 2 hours, placing it in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction is completed, adding 1 to 2 parts of hydrazine hydrate and stirring for 1 to 2 hours, and then centrifuging to obtain a supernatant, which is the boron quantum dot solution.
[0019] Preferably, the reaction temperature of the hydrothermal reaction is 180-185° C., and the reaction time is 10-12 h.
[0020] The surface of basalt fiber becomes rough after alkali etching, with pits or flaky protrusions appearing, which can increase the friction between sound waves and fibers, convert more sound energy into heat energy, thereby attenuating sound waves and improving the sound absorption coefficient.
[0021] As a preferred technical solution of the present invention, the silica sol is a modified silica sol; the preparation method of the modified silica sol comprises: in parts by weight, 10 to 15 parts of ethyl orthosilicate, 6 to 8 parts of paraffin, 15 to 20 parts of anhydrous ethanol and 15 to 20 parts of deionized water are mixed evenly, stirred at 45 to 50° C. for 20 to 30 minutes, adjusted to pH 4 to 5 with a 1 mol / L hydrochloric acid solution and stirred for 2 to 4 hours, then added with 20 to 30 parts of a 0.1 mol / L magnesium chloride solution, stirred at 50 to 65° C. for 3 to 5 hours, then dripped with ammonia water to adjust the pH to 7 to 8, stirred for 1 to 2 hours to obtain the modified silica sol.
[0022] The paraffin in the modified silica sol can absorb a large amount of heat during the transition from solid to liquid, thereby effectively reducing temperature fluctuations and improving the thermal insulation effect. At the same time, magnesium hydroxide grows in situ on the surface of the silica. Magnesium hydroxide can form a dense protective layer at high temperatures, covering the surface of the material, preventing the transfer of oxygen and heat, and improving the flame retardant effect.
[0023] As a preferred technical solution of the present invention, the graphene oxide is nitrogen-doped porous graphene oxide; the preparation method of the nitrogen-doped porous graphene oxide comprises: adding 15 to 20 parts of zinc gluconate and 1 to 3 parts of graphene oxide to 30 to 40 parts of deionized water, mixing evenly, reacting at 160 to 165° C. for 10 to 12 hours, filtering after cooling to room temperature, and freeze-drying the filter residue to obtain an intermediate product; mixing 2 to 4 parts of the intermediate product and 10 to 15 parts of urea and placing them in a tubular furnace, treating them at 750 to 800° C. for 2 to 4 hours under the protection of a nitrogen atmosphere, cooling to room temperature, washing, and drying to obtain nitrogen-doped porous graphene oxide.
[0024] Nitrogen-doped porous graphene oxide has a porous structure, which can complicate the internal pore structure, increase the refraction and reflection of sound waves inside the fiber, and more easily cause the vibration of the pore wall, increasing the loss of sound waves inside the material, thereby improving the sound absorption coefficient; in addition, the porous structure also increases the complexity of the heat conduction path, so that heat needs to pass through more paths and interfaces during the transfer process, effectively preventing the transfer of heat, thereby reducing the thermal conductivity.
[0025] The second aspect of the present invention provides a flame retardant, heat insulating and sound absorbing composite material prepared by the method described in the first aspect.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The composite material of the present invention introduces titanium element by modifying glass fiber, and the titanium-based material can absorb heat at high temperature, reduce the temperature of the material, and slow down the combustion speed; the boron element is introduced by modifying basalt fiber with boron quantum dots, and the boron element can form a glassy inorganic expansion coating covering the surface of the material to prevent the diffusion of combustible gas; the magnesium element is introduced by modifying silica sol, and the magnesium-based material can form a dense protective layer covering the surface of the material at high temperature to prevent the transfer of oxygen and heat; the nitrogen element is introduced by nitrogen-doped porous graphene oxide, and the nitrogen element can promote the formation of an expanded porous carbon layer, restricting the combustible gas from entering the gas phase to achieve the effect of heat insulation and oxygen isolation; the flame retardant performance is improved by the combined action of multiple elements such as titanium-boron-magnesium-nitrogen.
[0028] (2) The doping of rare earth elements in the phase change material of the present invention will introduce impurity atoms into the zirconium oxide lattice, causing lattice distortion and increasing the resistance of heat conduction, and cooperate with the paraffin in the modified silica sol to reduce temperature fluctuations, thereby obtaining a good thermal insulation effect;
[0029] (3) The rough surface of the boron quantum dot-modified basalt fiber after alkali etching can increase the friction between the sound wave and the fiber, so that more sound energy is converted into heat energy, thereby attenuating the sound wave, and work together with the porous structure of the nitrogen-doped porous graphene oxide to increase the refraction and reflection of the sound wave inside the composite material, increase the loss of the sound wave inside the material, and synergistically improve the sound absorption coefficient;
[0030] (4) The phase change material of the present invention uses rare earth modified zirconia. The doping of rare earth elements will introduce impurity atoms into the zirconia lattice, resulting in lattice distortion. These distortions will scatter phonons (heat energy carriers), increase the resistance to heat conduction, and thus reduce the thermal conductivity.
[0031] (5) The modified glass fiber of the present invention contains titanium dioxide, which can absorb heat at high temperatures, reduce the temperature of the material, and slow down the combustion rate. At the same time, the titanium element has a certain catalytic activity, which can catalyze the generation of non-combustible gas, dilute the concentration of combustible gas, inhibit combustion, and improve the oxygen index of the material. In addition, titanium dioxide particles can form tiny pores in the material, which are filled with air, which can increase the loss of sound waves inside the material, thereby improving the sound absorption coefficient;
[0032] (6) The surface of the basalt fiber of the present invention becomes rough after alkali etching, and pits or flaky protrusions appear, which can increase the friction between the sound wave and the fiber, so that more sound energy is converted into heat energy, thereby attenuating the sound wave, thereby improving the sound absorption coefficient;
[0033] (7) The paraffin in the modified silica sol of the present invention can absorb a large amount of heat during the transition from solid to liquid, thereby effectively reducing temperature fluctuations and improving the thermal insulation effect; at the same time, magnesium hydroxide grows in situ on the surface of the silica, and the magnesium hydroxide can form a dense protective layer at high temperature, covering the surface of the material, preventing the transfer of oxygen and heat, and improving the flame retardant effect;
[0034] (8) The nitrogen-doped porous graphene oxide of the present invention has a porous structure. The porous structure can complicate the internal pore structure, increase the refraction and reflection of sound waves inside the fiber, and more easily cause the vibration of the pore wall, thereby increasing the loss of sound waves inside the material, thereby improving the sound absorption coefficient; in addition, the porous structure also increases the complexity of the heat conduction path, so that heat needs to pass through more paths and interfaces during the transfer process, effectively preventing the transfer of heat, thereby reducing the thermal conductivity. DETAILED DESCRIPTION
[0035] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0036] The sources of some components in the embodiments and comparative examples are as follows:
[0037] Zirconium oxide, CAS No. 1314-23-4, purchased from Shanghai Huayuan Century Trading Co., Ltd.;
[0038] Glass fiber A, model EMG-250, length 80 μm, diameter 5 μm, purchased from Nanjing Glass Fiber Research and Design Institute;
[0039] Glass fiber B, model T435N, length 3 mm, diameter 12 μm, purchased from Taishan Glass Fiber Co., Ltd.;
[0040] Basalt fiber, product number FD2706, was purchased from Shandong Oude Chemical Fiber Products Co., Ltd.;
[0041] Silica sol, product number sy07, purchased from Qingdao Shuoyuan Silica Gel Technology Co., Ltd.;
[0042] Graphene oxide, model DN-20DY, was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.;
[0043] Zirconium oxychloride, CAS No. 13520-92-8, purchased from Shanghai Huayuan Century Trading Co., Ltd.;
[0044] Gadolinium nitrate, CAS No. 94219-55-3, was purchased from Shanghai Huayuan Century Trading Co., Ltd.;
[0045] Polyethylene glycol, catalog number PA73288, was purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0046] Sulfuric acid, CAS No. 7664-93-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0047] Tetrabutyl titanate, product number PA86584, was purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0048] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0049] Acetylacetone, CAS No. 123-54-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0050] Nitric acid, CAS No. 7697-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0051] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0052] Ammonium pentaborate, CAS No. 12007-89-5, purchased from Merck Chemical Co., Ltd.;
[0053] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0054] Hydrazine hydrate, CAS No. 7803-57-8, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0055] Ethyl orthosilicate, CAS No. 78-10-4, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0056] Paraffin wax, product number 4100511, was purchased from Shandong Yousuo Chemical Technology Co., Ltd.;
[0057] Hydrochloric acid, CAS No. 7647-01-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0058] Magnesium chloride, CAS No. 7786-30-3, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0059] Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0060] Zinc gluconate, CAS No. 4468-02-4, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0061] Urea, CAS No. 58069-82-2, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0062] Example 1
[0063] This embodiment provides a method for preparing a flame retardant, heat insulating and sound absorbing composite material, comprising the following steps:
[0064] Preparation of modified glass fiber: (1) By weight, 8 parts of phytic acid were added to 100 parts of deionized water to fully dissolve, and then 15 parts of glass fiber (glass fiber A, model EMG-250, length 80μm, diameter 5μm) were added to soak for 15 minutes, and after soaking, they were washed with deionized water and dried to obtain acidified glass fiber. (2) By weight, 6 parts of tetrabutyl titanate were added to 25 parts of anhydrous ethanol to fully dissolve, and then 3 parts of acetylacetone and 15 parts of deionized water were added to stir for 30 minutes, and then 8 parts of nitric acid solution with a molar concentration of 1 mol / L were added to stir for 2 hours to obtain a sol solution; 15 parts of the acidified glass fiber and 20 parts of anhydrous ethanol were added to 50 parts of the sol solution, stirred for 60 minutes, and allowed to stand for 4 hours. After removing the upper liquid, a precipitate was obtained, and the precipitate was washed with anhydrous ethanol and deionized water in turn, and dried at 75°C for 60 minutes to obtain a modified glass fiber.
[0065] Preparation of boron quantum dot modified basalt fiber: (1) By weight, add 4 parts of ammonium pentaborate and 2 parts of boric acid to 25 parts of deionized water and stir for 2 hours, place in argon atmosphere for hydrothermal reaction (reaction temperature is 180°C, reaction time is 12 hours), cool to room temperature after the reaction, add 2 parts of hydrazine hydrate and stir for 2 hours, then centrifuge to obtain supernatant, which is the boron quantum dot solution. (2) By weight, add 15 parts of basalt fiber to 100 parts of 1 mol / L sodium hydroxide solution, soak at 50°C for 2 hours, wash with deionized water 3 times after soaking to obtain roughened basalt fiber; add 15 parts of roughened basalt fiber to 25 parts of boron quantum dot solution and stir for 60 minutes, freeze-dry to obtain boron quantum dot modified basalt fiber.
[0066] Preparation of modified silica sol: In parts by weight, 15 parts of ethyl orthosilicate, 8 parts of paraffin, 20 parts of anhydrous ethanol and 20 parts of deionized water were mixed evenly, stirred at 50°C for 20 minutes, the pH was adjusted to 5 with a 1 mol / L hydrochloric acid solution and stirred for 4 hours, then 30 parts of a 0.1 mol / L magnesium chloride solution were added, stirred at 50°C for 5 hours, and then ammonia water was added dropwise to adjust the pH to 8, and the reaction was stirred for 2 hours to obtain a modified silica sol.
[0067] The preparation method of nitrogen-doped porous graphene oxide comprises: adding 20 parts of zinc gluconate and 3 parts of graphene oxide to 40 parts of deionized water by weight, mixing evenly, reacting at 160° C. for 12 hours, filtering after cooling to room temperature, and freeze-drying the filter residue to obtain an intermediate product; mixing 4 parts of the intermediate product and 15 parts of urea and placing them in a tubular furnace, treating them at 800° C. for 2 hours under the protection of a nitrogen atmosphere, cooling to room temperature, washing, and drying to obtain nitrogen-doped porous graphene oxide.
[0068] Step S1: In parts by weight, 12 parts of zirconium oxychloride, 8 parts of gadolinium nitrate, and 5 parts of polyethylene glycol are added to 100 parts of deionized water and mixed evenly, 25 parts of a 2 mol / L sulfuric acid solution are added at 85° C., and then the temperature is raised to 150° C. for hydrothermal reaction for 6 hours. After the reaction is completed, the mixture is cooled to room temperature, ammonia water is added to adjust the pH to 7.8, centrifuged, washed, and dried to obtain a phase change material;
[0069] Step S2: In parts by weight, 25 parts of modified glass fiber and 15 parts of boron quantum dot-modified basalt fiber are added to 20 parts of modified silica sol and stirred for 30 minutes, then 6 parts of the phase change material and 3 parts of nitrogen-doped porous graphene oxide are added and stirred for 40 minutes, and a first aging treatment is performed for 24 hours, and then 30 parts of anhydrous ethanol are added for a second aging treatment for 30 hours, and dried at 90°C for 6 hours to obtain a flame retardant, heat-insulating and sound-absorbing composite material.
[0070] Example 2
[0071] This embodiment provides a method for preparing a flame retardant, heat insulating and sound absorbing composite material, comprising the following steps:
[0072] Preparation of modified glass fiber: (1) By weight, 5 parts of phytic acid were added to 90 parts of deionized water to fully dissolve, and then 10 parts of glass fiber (glass fiber A, model EMG-250, length 80μm, diameter 5μm) were added to soak for 15 minutes, and after soaking, they were washed with deionized water and dried to obtain acidified glass fiber. (2) By weight, 4 parts of tetrabutyl titanate were added to 20 parts of anhydrous ethanol to fully dissolve, and then 1 part of acetylacetone and 10 parts of deionized water were added and stirred for 20 minutes, and then 6 parts of nitric acid solution with a molar concentration of 1 mol / L were added and stirred for 1 hour to obtain a sol solution; 10 parts of the acidified glass fiber and 15 parts of anhydrous ethanol were added to 30 parts of the sol solution, stirred for 50 minutes, and allowed to stand for 2 hours. After removing the upper liquid, a precipitate was obtained, and the precipitate was washed with anhydrous ethanol and deionized water in turn, and dried at 75°C for 40 minutes to obtain a modified glass fiber.
[0073] Preparation of boron quantum dot modified basalt fiber: (1) By weight, add 2 parts of ammonium pentaborate and 1 part of boric acid to 20 parts of deionized water and stir for 1 hour, place in argon atmosphere for hydrothermal reaction (reaction temperature is 185°C, reaction time is 10 hours), cool to room temperature after the reaction, add 1 part of hydrazine hydrate and stir for 1 hour, then centrifuge to obtain supernatant, which is the boron quantum dot solution. (2) By weight, add 10 parts of basalt fiber to 80 parts of 1 mol / L sodium hydroxide solution, soak at 40°C for 4 hours, wash with deionized water 3 times after soaking to obtain roughened basalt fiber; add 10 parts of roughened basalt fiber to 20 parts of boron quantum dot solution and stir for 40 minutes, freeze-dry to obtain boron quantum dot modified basalt fiber.
[0074] Preparation of modified silica sol: In parts by weight, 10 parts of ethyl orthosilicate, 6 parts of paraffin, 15 parts of anhydrous ethanol and 15 parts of deionized water were mixed evenly, stirred at 45°C for 30 minutes, the pH was adjusted to 4 with a 1 mol / L hydrochloric acid solution and stirred for 2 hours, then 20 parts of a 0.1 mol / L magnesium chloride solution were added, stirred at 65°C for 3 hours, and then ammonia water was added dropwise to adjust the pH to 7, and the reaction was stirred for 1 hour to obtain a modified silica sol.
[0075] The preparation method of nitrogen-doped porous graphene oxide comprises: adding 15 parts of zinc gluconate and 1 part of graphene oxide to 30 parts of deionized water, mixing evenly, reacting at 165° C. for 10 hours, filtering after cooling to room temperature, and freeze-drying the filter residue to obtain an intermediate product; mixing 2 parts of the intermediate product and 10 parts of urea and placing them in a tubular furnace, treating them at 750° C. for 4 hours under the protection of a nitrogen atmosphere, cooling to room temperature, washing, and drying to obtain nitrogen-doped porous graphene oxide.
[0076] Step S1: In parts by weight, 10 parts of zirconium oxychloride, 6 parts of gadolinium nitrate, and 3 parts of polyethylene glycol are added to 80 parts of deionized water and mixed evenly, 20 parts of a 2 mol / L sulfuric acid solution are added at 80° C., and then the temperature is raised to 145° C. for hydrothermal reaction for 6 hours. After the reaction is completed, the mixture is cooled to room temperature, ammonia water is added to adjust the pH to 7.5, centrifuged, washed, and dried to obtain a phase change material;
[0077] Step S2: In parts by weight, 20 parts of modified glass fiber and 10 parts of boron quantum dot-modified basalt fiber are added to 15 parts of modified silica sol and stirred for 20 minutes, then 4 parts of the phase change material and 1 part of nitrogen-doped porous graphene oxide are added and stirred for 30 minutes, and a first aging treatment is performed for 20 hours, and then 20 parts of anhydrous ethanol are added for a second aging treatment for 26 hours, and dried at 80°C for 8 hours to obtain a flame retardant, heat-insulating and sound-absorbing composite material.
[0078] Example 3
[0079] This embodiment provides a method for preparing a flame retardant, heat insulating and sound absorbing composite material, comprising the following steps:
[0080] Preparation of modified glass fiber: (1) By weight, 6 parts of phytic acid were added to 95 parts of deionized water to fully dissolve, and then 12 parts of glass fiber (glass fiber A, model EMG-250, length 80μm, diameter 5μm) were added to soak for 12 minutes, and after soaking, they were washed with deionized water and dried to obtain acidified glass fiber. (2) By weight, 5 parts of tetrabutyl titanate were added to 22 parts of anhydrous ethanol to fully dissolve, and then 2 parts of acetylacetone and 12 parts of deionized water were added and stirred for 25 minutes, and then 7 parts of nitric acid solution with a molar concentration of 1 mol / L were added and stirred for 2 hours to obtain a sol solution; 12 parts of the acidified glass fiber and 18 parts of anhydrous ethanol were added to 40 parts of the sol solution, stirred for 55 minutes, and allowed to stand for 3 hours. After removing the upper liquid, a precipitate was obtained, and the precipitate was washed with anhydrous ethanol and deionized water in turn, and dried at 72°C for 50 minutes to obtain a modified glass fiber.
[0081] Preparation of boron quantum dot modified basalt fiber: (1) By weight, add 3 parts of ammonium pentaborate and 2 parts of boric acid to 22 parts of deionized water and stir for 2 hours, place in argon atmosphere for hydrothermal reaction (reaction temperature is 180°C, reaction time is 12 hours), cool to room temperature after the reaction, add 2 parts of hydrazine hydrate and stir for 2 hours, then centrifuge to obtain supernatant, which is the boron quantum dot solution. (2) By weight, add 15 parts of basalt fiber to 100 parts of 1 mol / L sodium hydroxide solution, soak at 50°C for 2 hours, wash with deionized water 3 times after soaking to obtain roughened basalt fiber; add 15 parts of roughened basalt fiber to 25 parts of boron quantum dot solution and stir for 60 minutes, freeze-dry to obtain boron quantum dot modified basalt fiber.
[0082] Preparation of modified silica sol: In parts by weight, 15 parts of ethyl orthosilicate, 8 parts of paraffin, 20 parts of anhydrous ethanol and 20 parts of deionized water were mixed evenly, stirred at 50°C for 20 minutes, the pH was adjusted to 5 with a 1 mol / L hydrochloric acid solution and stirred for 4 hours, then 30 parts of a 0.1 mol / L magnesium chloride solution were added, stirred at 50°C for 5 hours, and then ammonia water was added dropwise to adjust the pH to 8, and the reaction was stirred for 2 hours to obtain a modified silica sol.
[0083] The preparation method of nitrogen-doped porous graphene oxide comprises: adding 20 parts of zinc gluconate and 3 parts of graphene oxide to 40 parts of deionized water by weight, mixing evenly, reacting at 160° C. for 12 hours, filtering after cooling to room temperature, and freeze-drying the filter residue to obtain an intermediate product; mixing 4 parts of the intermediate product and 15 parts of urea and placing them in a tubular furnace, treating them at 800° C. for 2 hours under the protection of a nitrogen atmosphere, cooling to room temperature, washing, and drying to obtain nitrogen-doped porous graphene oxide.
[0084] Step S1: by weight, 11 parts of zirconium oxychloride, 7 parts of gadolinium nitrate, and 4 parts of polyethylene glycol are added to 90 parts of deionized water and mixed evenly, 22 parts of a 2 mol / L sulfuric acid solution are added at 82° C., and then the temperature is raised to 148° C. for hydrothermal reaction for 7 hours. After the reaction is completed, the mixture is cooled to room temperature, ammonia water is added to adjust the pH to 7.6, centrifuged, washed, and dried to obtain a phase change material;
[0085] Step S2: In parts by weight, 222 parts of modified glass fiber and 14 parts of boron quantum dot-modified basalt fiber are added to 18 parts of modified silica sol and stirred for 25 minutes, then 5 parts of the phase change material and 2 parts of nitrogen-doped porous graphene oxide are added and stirred for 35 minutes, and a first aging treatment is performed for 22 hours, and then 25 parts of anhydrous ethanol are added for a second aging treatment for 28 hours, and dried at 85°C for 7 hours to obtain a flame retardant, heat-insulating and sound-absorbing composite material.
[0086] Comparative Example 1
[0087] This comparative example provides a method for preparing a sound-absorbing composite material, which differs from Example 1 in that commercially available zirconium oxide is used instead of the phase change material, commercially available glass fiber A is used instead of the modified glass fiber, commercially available basalt fiber is used instead of the boron quantum dot-modified basalt fiber, commercially available silica sol is used instead of the modified silica sol, and commercially available graphene oxide is used instead of the nitrogen-doped porous graphene oxide.
[0088] Comparative Example 2
[0089] This comparative example provides a method for preparing a sound-absorbing composite material, which differs from comparative example 1 in that a phase change material is used instead of commercially available zirconium oxide.
[0090] Comparative Example 3
[0091] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from comparative example 1 in that modified glass fiber is used instead of commercially available glass fiber A.
[0092] Comparative Example 4
[0093] This comparative example provides a method for preparing a sound-absorbing composite material, which differs from comparative example 3 in that commercially available glass fiber B (model T435N, length 3 mm, diameter 12 μm) is used instead of commercially available glass fiber A (model EMG-250, length 80 μm, diameter 5 μm) to prepare the modified glass fiber.
[0094] Comparative Example 5
[0095] This comparative example provides a method for preparing a sound-absorbing composite material, which differs from comparative example 1 in that boron quantum dot-modified basalt fibers are used instead of commercially available basalt fibers.
[0096] Comparative Example 6
[0097] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from comparative example 1 in that modified silica sol is used instead of commercially available silica sol.
[0098] Comparative Example 7
[0099] This comparative example provides a method for preparing a sound-absorbing composite material, which differs from comparative example 1 in that nitrogen-doped porous graphene oxide is used instead of commercially available graphene oxide.
[0100] Comparative Example 8
[0101] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from Example 1 in that commercially available zirconium oxide is used instead of the phase change material.
[0102] Comparative Example 9
[0103] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from Example 1 in that commercially available glass fiber A is used instead of the modified glass fiber.
[0104] Comparative Example 10
[0105] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from Example 1 in that commercially available basalt fibers are used instead of boron quantum dot-modified basalt fibers.
[0106] Comparative Example 11
[0107] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from Example 1 in that commercially available silica sol is used instead of modified silica sol.
[0108] Comparative Example 12
[0109] This comparative example provides a method for preparing a sound-absorbing composite material, which is different from Example 1 in that commercially available graphene oxide is used instead of nitrogen-doped porous graphene oxide.
[0110] The performance of the sound-absorbing composite materials provided in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0111] (1) Flame retardancy test: refer to the requirements of GB / T 8924-2005 Test method for combustion performance of fiber reinforced plastics - oxygen index method for testing.
[0112] (2) Thermal conductivity test: Test according to the requirements of GB / T 10295-2008 Determination of steady-state thermal resistance and related properties of insulation materials - Heat flow meter method.
[0113] (3) Sound absorption coefficient test: Test according to the requirements of GB / T 18696.2-2002 Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 2: Transfer function method.
[0114] The above performance test data is shown in Table 1.
[0115] Table 1 Performance test results
[0116]
[0117]
[0118] From the above content, it can be seen that the present invention prepares a flame retardant, heat insulating and sound absorbing composite material (Examples 1 to 3) by modifying the glass fiber in the composite material, adding a phase change material, and introducing modified components such as boron quantum dot modified basalt fiber, modified silica sol and nitrogen-doped porous graphene oxide. The oxygen index of the composite material is 41.4 to 41.8%, the thermal conductivity is 0.021 to 0.025 W / (m·K), and the sound absorption coefficient (@2000Hz) is 0.91 to 0.96.
[0119] Compared with Example 1, commercially available zirconium oxide is used instead of phase change material, commercially available glass fiber A is used instead of modified glass fiber, commercially available basalt fiber is used instead of boron quantum dot modified basalt fiber, commercially available silica sol is used instead of modified silica sol, and commercially available graphene oxide is used instead of nitrogen-doped porous graphene oxide, then the oxygen index becomes smaller, the thermal conductivity is increased, and the sound absorption coefficient is reduced (Comparative Example 1); compared with Comparative Example 1, the phase change material is used instead of commercially available zirconium oxide, then the thermal conductivity is reduced (Comparative Example 2); compared with Comparative Example 1, the modified glass fiber is used instead of the commercially available glass fiber A, The oxygen index becomes larger and the sound absorption coefficient increases (Comparative Example 3); Compared with Comparative Example 3, commercially available glass fiber B (model T435N, length 3mm, diameter 12μm) is used to replace commercially available glass fiber A (model EMG-250, length 80μm, diameter 5μm) for the preparation of modified glass fiber. Since the length and diameter of the commercially available glass fiber B exceed the protection scope of the present invention, the modification effect is not good, so the oxygen index becomes smaller and the sound absorption coefficient decreases (Comparative Example 4); Compared with Comparative Example 1, boron quantum dot modified basalt fiber is used to replace commercially available basalt fiber. , the sound absorption coefficient increases (Comparative Example 5); compared with Comparative Example 1, modified silica sol is used to replace the commercially available silica sol, the oxygen index becomes larger, and the thermal conductivity decreases (Comparative Example 6); compared with Comparative Example 1, nitrogen-doped porous graphene oxide is used to replace the commercially available graphene oxide, the thermal conductivity decreases, and the sound absorption coefficient increases (Comparative Example 7); compared with Example 1, commercially available zirconium oxide is used to replace the phase change material, the oxygen index becomes smaller, the thermal conductivity increases, and the sound absorption coefficient decreases (Comparative Example 8); compared with Example 1, commercially available glass fiber A is used to replace the modified glass fiber, the oxygen index becomes Compared with Example 1, when commercially available basalt fiber is used instead of boron quantum dot modified basalt fiber, the oxygen index becomes smaller, the thermal conductivity is increased, and the sound absorption coefficient is reduced (Comparative Example 9); compared with Example 1, when commercially available basalt fiber is used instead of boron quantum dot modified basalt fiber, the oxygen index becomes smaller, the thermal conductivity is increased, and the sound absorption coefficient is reduced (Comparative Example 10); compared with Example 1, when commercially available silica sol is used instead of modified silica sol, the oxygen index becomes smaller, the thermal conductivity is increased, and the sound absorption coefficient is reduced (Comparative Example 11); compared with Example 1, when commercially available graphene oxide is used instead of nitrogen-doped porous graphene oxide, the oxygen index becomes smaller, the thermal conductivity is increased, and the sound absorption coefficient is reduced (Comparative Example 12).
[0120] In summary, the present invention modifies the glass fiber in the composite material, adds phase change material, and introduces modified components such as boron quantum dot-modified basalt fiber, modified silica sol and nitrogen-doped porous graphene oxide. Through the synergistic effect of each component, the thermal conductivity of the composite material is reduced, and the flame retardant performance and sound absorption effect are improved.
[0121] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a flame retardant, heat insulating and sound absorbing composite material, characterized in that: The following steps are involved: Step S1: by weight, 10 to 12 parts of zirconium oxychloride, 6 to 8 parts of gadolinium nitrate, and 3 to 5 parts of polyethylene glycol are added to 80 to 100 parts of deionized water and mixed evenly, 20 to 25 parts of a 2 mol / L sulfuric acid solution are added at 80 to 85° C., and then the temperature is raised to 145 to 150° C. for hydrothermal reaction for 6 to 8 hours. After the reaction is completed, the mixture is cooled to room temperature, ammonia water is added to adjust the pH to 7.5 to 7.8, centrifuged, washed, and dried to obtain a phase change material; Step S2: In parts by weight, 20 to 25 parts of modified glass fiber and 10 to 15 parts of basalt fiber are added to 15 to 20 parts of silica sol and stirred for 20 to 30 minutes, then 4 to 6 parts of the phase change material and 1 to 3 parts of graphene oxide are added and stirred for 30 to 40 minutes, a first aging treatment is performed for 20 to 24 hours, and then 20 to 30 parts of anhydrous ethanol are added for a second aging treatment for 26 to 30 hours, and dried at 80 to 90° C. for 6 to 8 hours to obtain the flame retardant, heat insulating and sound absorbing composite material.
2. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises: adding 4 to 6 parts of tetrabutyl titanate to 20 to 25 parts of anhydrous ethanol by weight to fully dissolve, then adding 1 to 3 parts of acetylacetone and 10 to 15 parts of deionized water and stirring for 20 to 30 minutes, then adding 6 to 8 parts of nitric acid solution with a molar concentration of 1 mol / L, stirring for 1 to 2 hours to obtain a sol solution; adding 10 to 15 parts of acidified glass fiber and 15 to 20 parts of anhydrous ethanol to 30 to 50 parts of the sol solution, stirring for reaction for 50 to 60 minutes, standing for 2 to 4 hours, removing the upper layer of liquid to obtain a precipitate, washing the precipitate with anhydrous ethanol and deionized water in turn, and drying at 70 to 75° C. for 40 to 60 minutes to obtain the modified glass fiber.
3. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 2, characterized in that: The acidified glass fiber is obtained by subjecting glass fiber to an acidification treatment.
4. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 3, characterized in that: The glass fiber has a length of 50 to 300 μm and a diameter of 4 to 6 μm.
5. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 1, characterized in that: The basalt fiber is boron quantum dot modified basalt fiber; The preparation method of the boron quantum dot modified basalt fiber comprises: adding 10 to 15 parts of basalt fiber to 80 to 100 parts of sodium hydroxide solution with a molar concentration of 1 mol / L by weight, soaking for 2 to 4 hours at 40 to 50° C., washing with deionized water for 3 times after soaking to obtain roughened basalt fiber; adding 10 to 15 parts of the roughened basalt fiber to 20 to 25 parts of boron quantum dot solution, stirring for 40 to 60 minutes, and freeze-drying to obtain the boron quantum dot modified basalt fiber.
6. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 5, characterized in that: The preparation method of the boron quantum dot solution comprises: adding 2 to 4 parts of ammonium pentaborate and 1 to 2 parts of boric acid to 20 to 25 parts of deionized water by weight, stirring for 1 to 2 hours, placing in an argon atmosphere for hydrothermal reaction, cooling to room temperature after the reaction is completed, adding 1 to 2 parts of hydrazine hydrate, stirring for 1 to 2 hours, and then centrifuging to obtain a supernatant, which is the boron quantum dot solution.
7. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 6, characterized in that: The reaction temperature of the hydrothermal reaction is 180-185° C., and the reaction time is 10-12 hours.
8. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 1, characterized in that: The silica sol is a modified silica sol; The preparation method of the modified silica sol comprises: mixing 10 to 15 parts of ethyl orthosilicate, 6 to 8 parts of paraffin, 15 to 20 parts of anhydrous ethanol and 15 to 20 parts of deionized water in parts by weight, stirring for 20 to 30 minutes at 45 to 50° C., adjusting the pH to 4 to 5 with a hydrochloric acid solution with a molar concentration of 1 mol / L and stirring for 2 to 4 hours, then adding 20 to 30 parts of a magnesium chloride solution with a molar concentration of 0.1 mol / L, stirring for 3 to 5 hours at 50 to 65° C., then dropping ammonia water to adjust the pH to 7 to 8, stirring for 1 to 2 hours to obtain the modified silica sol.
9. The method for preparing a flame retardant, heat insulating and sound absorbing composite material according to claim 1, characterized in that: The graphene oxide is nitrogen-doped porous graphene oxide; The preparation method of the nitrogen-doped porous graphene oxide comprises: adding 15 to 20 parts of zinc gluconate and 1 to 3 parts of graphene oxide to 30 to 40 parts of deionized water by weight, mixing evenly, reacting at 160 to 165° C. for 10 to 12 hours, filtering after cooling to room temperature, and freeze-drying the filter residue to obtain an intermediate product; mixing 2 to 4 parts of the intermediate product and 10 to 15 parts of urea and placing them in a tubular furnace, treating them at 750 to 800° C. for 2 to 4 hours under the protection of a nitrogen atmosphere, cooling to room temperature, washing, and drying to obtain the nitrogen-doped porous graphene oxide.
10. A flame retardant, heat insulating and sound absorbing composite material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of nanometer zirconia heat barrier coating
CN101660115A
Preparation method of glass fiber titanium-dioxide-loaded composite material
CN103433013A
Sound-absorbing material and preparation method thereof
CN106782476A
High-strength glass fiber composite material and preparation method thereof
CN111517748A
CPET plastic box material for food, preparation method of CPET plastic box material and plastic box for food
CN116987368A
Cited By
Glass fiber sound-absorbing cold-proof heat-insulating felt and preparation method thereof
CN120058274A
Rigid noise-reduction rock wool board for ships and preparation method of rigid noise-reduction rock wool board
CN121340766A